Analysis of the needs of science, technology, engineering and mathematics (STEM) learning instruments on the derivative topic. (February 2020) - Husna, R; Johar, R; Usman
Abstract: STEM (Science, Technology, Engineering, and Mathematics) is an approach which combines or fuses science, technology, engineering, and mathematics into education program to improve students' learning potential. STEM is started to be disseminated by the government to provide a push for the realization of Industrial Revolution 4.0 in this century. The purpose of this study is to describe the necessity of STEM learning instruments on the derivative topic. This study is part of the developmental research on the preliminary stage, which is the needs analysis. Three of eleventh-grade math teachers were invited to participate in this study. The questionnaire about various aspects of the needs analysis was given to the teachers. The study results found that the teachers agree to develop STEM learning instruments on the derivative topic and are interested in examining the instruments if they are accessible for them.